THE ROLE OF VALUES IN THE FORMATION OF ECOLOGICAL CULTURE IN STUDENTS - Dildora Abdurakhmanovna Mahkamova (European Science Publishing, 2024)
The article expresses an opinion on the role of values in the formation of ecological culture among students of secondary schools in the context of ecological globalization. The development of environmental education in general education schools in Uzbekistan is described as important, taking into account and mutual integration of the three basic values.
Keywords: Ecology, value, environmental education, environmental awareness, religious values, national values, environmental safety, environmental identity, civilization.